Microemulsions : a new perspective in the treatment of paediatric and geriatric tuberculosis patients - Wisch, Michael Henry (Rhodes University, Faculty of Pharmacy, Pharmacy, 2000)
Tuberculosis(TB) was declared to be a global emergency in 1993, with South Africa declaring it to be the country's top health priority in 1996, but ineffective treatment strategies have led to fewer than half of all treated patients in South Africa being cured. At present,paediatric treatment remains a problem, as the antitubercular preparations of rifampicin, isoniazid and pyrazinamide, that are currently available, were not initially designed for the treatment of paediatric TB patients, providing a motivation for this project. The aim of this project is thus the development of a microemulsion dosage form for the oral delivery of RIF(Rifampicin), INH(Isoniazid) and PZA(Pyrazinamide) in combination. RIF, INH and PZA were adequately characterised with reference to the monograph standards referenced and were found to be sufficiently pure to be used in subsequent work. A chromatographic system and conditions were selected and validated as being optimal for HPLC analysis of RIF, INH and PZA in combination, with a drug partitioning method for miglyol 812 developed and validated. Ternary and pseudo-ternary phase diagrams were constructed and reported, all employing miglyol 812 as the lipid. It was undoubtedly the imwitor 308 and crillet 3 combination o/w microemulsion system that proved most successful, maintaining homogeneity on dilution. The microemulsion used in formulation comprised imwitor 308 (27.63%), crillet 3 (27.63%), miglyol 812 23.68%) and water (21.06%). The stability of RIF, INH and PZA was investigated in aqueous solution, miglyol 812, corn oil, 10%m/v cremophor RH, 5%m/v imwitor 308, 10%m/v crillet 3 and 70%m/v sorbitol solution. Trends in the stability assessments conducted on RIF, INH and PZA were noted, with slight variation depending on the formulation component being evaluated. RIF invariably demonstrated temperature and oxidation dependent degradation in all vehicles, with a definite distinction possible between samples stored at 25, 40 and 600C over a 7 day trial period. A definite advantage of storing RIF solutions under nitrogen was observed, with these solutions showing less degradation over the course of the trial, than those stored under air. INH produced a pronounced increase in the degree of degradation of RIF, whereas PZA had a negligible effect on it's stability. INH proved to be most stable in the 70%m/v sorbitol solution with no significant oxidation or temperature dependent degradation indicated. Temperature dependent degradation was only noticable when INH was in combination with RIF, most significant in crillet 3 solution. PZA was the most stable of the three drugs, remaining relatively unaffected by temperature and the presence of air, independent of the vehicle employed, although the drug remaining did decrease slightly in the presence of RIF.Due to drug dose specifications and solubility limitations, the final formulation assessed, only contained RIF and INH, despite INH and PZA having no significant effect on the stability of each other. The solubility of PZA in the lipid and aqueous components of the microemulsion was not great enough to achieve the required 500 mg/10ml dose, while RIF and INH could achieve the respective 150mg/10ml and 100mg/10ml dose. RIF stability was improved, as anticipated, with the incorporation of RIF into the internal phase decreasing contact with INH which has been shown to affect it's stability. RIF behaved as predicted, possessing greater stability than shown in the individual formulation components, however, INH did not, being less stable in formulation in the absence of antioxidant, than in it's presence. A novel microemulsion formulation capable of delivering the incompatible RIF and INH in combination, with numerous microemulsion systems mapped,with the ability of being used for the delivery of other lipophilic drugs and drug combinations, was produced.The final formulation provided valuable information into possible future improvements of the microemulsion to improve drug stability.
Keywords: Emulsions (Pharmacy); Tuberculosis -- Treatment -- South Africa; Tuberculosis in children -- Treatment; Tuberculosis in old age -- Treatment; Tuberculosis -- Treatment